(untitled) (Environment & Health, 2020)
The ecologically dependent diseases are gaining more and more weight in the structure of the general morbidity of the population, and as a result, there is a need to develop the scientific bases of the ecological safety of Ukraine, a methodology for provision and its implementation. Objective:We developed a conception and a methodology for the functional and ecological expertise (FEE) of the regions of radiological (ecological) control in Ukraine and a fast simple method for the assessment of the functional and vegetative health of children. It will make it possible to identify the areas with a high integral ecological load for a human and provide functional and vegetative certification of the children’s population. Methods: The FEE of the radiation control regions of Ukraine is based on the survey results of the functional and vegetative health of 18,650 children that lived in 92 settlements of the Vinnytsia (moderately contaminated), the Lviv (relatively clean) and the Chernihiv (strongly contaminated) oblasts of Ukraine in1993-2010. For this purpose, we used functional and vegetative diagnosis of the vegetative health of the children’s population after the V. Makats’ method, which makes it possible to reveal the indices of the dispersion of the vegetative levels which are the integral bioindicators of internal homeostasis. The integral features of the ecological state are formed on this basis and the zones of its ecological pressure are determined as well. Results:The FEE results of the Lviv oblast (2001-2006) showed a compliance with the criteria of the official dosimetric certification of the RS and the stable preference of the sympathetic activity in the children was revealed. According to the FEE results inthe Vinnytsia oblast (IV radiation control zone), only one case (Chervona Hreblia village, Chechelnytsk area) of a discordance with the official dosimetric certification criteria of the RS (according to the FEE, it is in the "Functional safety" zone) was revealed. The FEE confirms the classification of the number of RS in the Chernihiv oblast as "relatively radiation-free" ones. At the same time, in 2000, according to the functional health of children, the Borzna area (Borzna, Velyka Zahorivka, Shapovalivka) was assigned to the zone of " the development of functional strain" and the Ichnia area (Ichnia) - to the zone of the "development of functional catastrophe" (IV zone), which does not meet the criteria of the official dosimetric certification of the RS. Conclusions: The results of the FEE of the functional health levels, obtained at the contaminated territories of Ukraine, coincide with the data of the state radiological monitoring which indicates the effectiveness and reliability of the proposed FEE method. The FEE, as a method of bioindication, based on the functional and vegetative health of children under modern conditions, is a highly sensitive method for the identification of the environmental problems of the territories and it fundamentally complements the accepted forms of dosimetric and thyroid dosimetric control.